A comparison of reinforcement schedules to increase independent responding in individuals with intellectual disabilities. Issue 1 (23rd September 2013) - Hausman, Nicole L.; Ingvarsson, Einar T.; Kahng, SungWoo
<x xml:space="preserve">Abstract</x> We compared the effects of varying reinforcement schedules on independent responding with 3 individuals with intellectual disabilities. Independent responding was always reinforced, and responding after a vocal response was either (a) always reinforced, (b) never reinforced, or (c) reinforced on a fixed‐ratio 3 schedule. Results showed that for 2 of the 3 participants, independent responding was higher when responding after the vocal prompt was never reinforced. These data suggest that altering the reinforcement schedule to favor independent responding may lead to increased independent responding.